Comparing among the Experiences of Self-Cutting, Hitting, and Scratching in Chinese Adolescents Attending Secondary Schools: An Interview Study. (February 2015) - You, Jianing; Ma, Congfen; Lin, Min-Pei; Leung, Freedom
This study examined adolescents' experiences associated with nonsuicidal self-injury (NSSI) and compared among the experiences of self-cutting, hitting, and scratching. Participants included 42 Chinese adolescents attending secondary schools. They had at least three NSSI episodes in the preceding year. Information about their experiences of NSSI was assessed by structured interviews. Regardless of the methods, NSSI primarily served the affect regulation function and was usually preceded by negative affects and followed by positive affect. Additionally, as compared to self-hitting and scratching, self-cutting indicated a higher level of distress, resulted in less subjective feelings of pain, and was more likely to be performed to relieve dysphoric affects. This study suggests that different NSSI methods may signal different underlying psychopathologies.